THE BASIS OF CONCEPTION OF THE REGIONAL ECONOMY BRANCH RESTRUCTURIZATION - A. M. Tufetulov (Russian Journal of Economics and Law)
The article gives a thorough analysis of the mutual influence of the parameters of technical-economic paradigm on the formation and development of the branch restructurization processes in the regional economy within the «long wave» conception. The branch restructurization as a logical process of the economy cyclic development is viewed through the immanent basic constituents: the institutional, the branch and the technological reconstruction. Besides, the publication pays close attention to the conditions, stages and features of technological restructurization and the factors determining the technological setup. Thus, the success of the branch restructurization of regional economy depends to a large extent on the correctly chosen strategy of technological development.